PERLINDUNGAN KONSUMEN TERHADAP INFORMASI BUKA 24 JAM DI SPBU KOTA PEKANBARU - Doni Andrinal; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Article 4 Letter c The Consumer Protection Law stipulates that every consumer isentitled to correct, clear and honest information about the condition and guarantee ofgoods and / or services. In Article 7 Letter a UUPK stipulates that business actors areobliged to beriktikad both in conducting their business activities, including in providinginformation to consumers such as information open 24 hours. In Pekanbaru City thereare 47 Pertamina gas stations that operate every day and there are some gas stations thatexplain open 24 hours and there are 3 gas stations that the authors choose to be thelocation of research, but in reality SPBU is not operating in accordance with theinformation listed, so that the mistake information is detrimental to consumers . Thepurpose of writing this thesis, namely; First, To explain the rights and obligations ofconsumers and business actors, Secondly, the causes of gas stations do not operateaccording to the information provided to consumers, Third, Explain how theimplementation of legal protection against consumers due to untruthful informationprovided to consumers.This type of research can be classified in sociological studies. To obtain data inthe writing of this thesis is done literature research and field research. This research wasconducted at Gas Station Pertamina Pekanbaru City. While the population and thesample are all related to the problem studied in this research, the data source used, theprimary data and the secondary data, the data collecting technique in this research withobservation, interview, questionnaire, and literature study.Based on the results of the research problem there are three points that can beconcluded, First, the delivery of complete information, true, clear and honest is one of theobligations of business actors, otherwise the business actor's obligation is the consumer'sright. Second, the information contained in the gas station pamphlet due to externalconstraints such as security factors, area factors, human factors, and cultural factors.Third, Implementation Legal protection of consumers for untruthfulness of informationopen 24 hours on gas station pamphlets based on the reality in the field consumers do notget the right that is in the form of true information, clear and honest. SPBU parties thathave violated the rights of consumers may be subject to sanctions in the form ofreprimands for having provided false information. Suggestion Writer, First, it is expectedto the SPBU to update the information contained in the information pamphlet in order notto mislead the consumer. Secondly, to the owner of a gas station located in PekanbaruCity not to use the pamphlet is open 24 hours, because only gas stations that exist on thenational road that operates for 24 hours. Third, to consumers who feel aggrieved with theinformation to report to the Consumer Dispute Settlement Agency for business actors maybe subject to administrative sanctions and fine sanctions.Keywords: Protection - Consumers - Pertamina Gas Station - 24 Hours